DESIGN OF A DIGITAL CORRESPONDENCE AND DISPOSITION SYSTEM WITH INTEGRATED DIGITAL SIGNATURE - Kadek Rolavito Andrianto Putra; Ajeng Hidayati (Jurnal Riset Informatika, 2025)
The administrative workflow at the Army Communication and Electronics Center (PUSKOMLEKAD) faces significant challenges due to its reliance on manual, paper-based correspondence processes. This manual system causes operational inefficiencies, difficulties in real-time disposition tracking, and critical workflow bottlenecks, particularly the dependency on the physical presence of leadership for signatures. Data for this study were collected through direct observation of the manual administrative workflow and interviews with personnel regarding user requirements. The research method used is Research and Development (R&D), applying the Rapid Application Development (RAD) model for the system's lifecycle using the PHP Laravel framework and MySQL database. The research resulted in a functional prototype that features an integrated digital archive, a multi-level disposition system for real-time tracking, and a secure PIN-based digital signature. In conclusion, the integration of digital signatures effectively solves the primary bottleneck by eliminating the need for physical presence, thus significantly enhancing operational efficiency, transparency, and accountability at PUSKOMLEKAD.